1997
DOI: 10.1007/bf02439972
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective study of the hearing results obtained after stapedotomy by the implantation of two Teflon pistons with a different diameter

Abstract: Disclaimer/Complaints regulationsIf you believe that digital publication of certain material infringes any of your rights or (privacy) interests, please let the Library know, stating your reasons. In case of a legitimate complaint, the Library will make the material inaccessible and/or remove it from the website. Please Ask the Library: http://uba.uva.nl/en/contact, or a letter to: Library of the University of Amsterdam, Secretariat, Singel 425, 1012 WP Amsterdam, The Netherlands. You will be contacted as soon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 6 publications
1
35
0
1
Order By: Relevance
“…When relating the results of the present study, the results of Grolman et al [5] and the calculations of Rosowski and Merchant [1] to the surface area of the distal part of the stapes pistons in question, it appears that a doubling in the distal surface area leads to an improvement in the air conduction thresholds of 5-7 dB. Thus, a 0.6-mm piston has the potential of improving the hearing 5-7 dB over a 0.4-mm piston, and a 0.8-mm piston has the potential of improving the hearing 5-7 dB over a 0.6-mm piston for frequencies up to and including 2 kHz.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…When relating the results of the present study, the results of Grolman et al [5] and the calculations of Rosowski and Merchant [1] to the surface area of the distal part of the stapes pistons in question, it appears that a doubling in the distal surface area leads to an improvement in the air conduction thresholds of 5-7 dB. Thus, a 0.6-mm piston has the potential of improving the hearing 5-7 dB over a 0.4-mm piston, and a 0.8-mm piston has the potential of improving the hearing 5-7 dB over a 0.6-mm piston for frequencies up to and including 2 kHz.…”
Section: Discussionmentioning
confidence: 68%
“…When Fisch [4] did not find any difference between the results of 0.6-mm and 0.4-mm stapedotomy, the reason might be that he used the postoperative air bone gap as the decisive parameter. Grolman et al [5] compared the results with an all-Teflon piston with a shaft diameter of 0.3 and of 0.4 mm in randomly selected patients. They found a statistically significant difference in the gain in air conduction thresholds for frequencies between 125 Hz, 250 Hz, 500 Hz and 1 kHz.…”
Section: Discussionmentioning
confidence: 99%
“…Grolman et al, [11] compared 0.3 and 0.4 mm Teflon piston and found that 0.4 mm piston has a better postsurgical hearing result in the low frequencies. Marquet and Creten [12] reported ineffective air-bone gap closure at lower frequencies with 0.6 mm piston.…”
Section: Discussionmentioning
confidence: 98%
“…Similarly, Sennaroglu et al [11] , Grolman et al [12] and Marchese et al [13] when they compared the functional capacity of prostheses with 0.6-0.8, 0.3-0.4 and 0.4-0.6 mm, respectively, concluded that larger diameter prostheses led to greater improvement in hearing especially at lower frequencies. This theory could be explained by the experimental model of Rosowski and Merchant [14] , which showed that a high relationship between the prosthesis diameter and oval window surface gives the system better compliance at low frequencies.…”
Section: Discussionmentioning
confidence: 99%